Evolutionary analysis of TSP-1 gene in Plateau zokor (MyospalaxBaileyi) and its expression pattern under hypoxia - Li, Suhua; Xu, Bo; An, Zhifang; Wang, Zhijie; Li, Yongxiao; Wei, Lian; Wei, Dengbang (Cellular and Molecular Biology, 2019)
The plateau zokor (Myospalaxbaileyi) is a specialized subterranean rodent that lives on the Qinghai-Tibet Plateau, and has successfully adapted to hypoxic environment. Raised expression of vascular endothelial growth factor (VEGF) and enhanced microvessel density (MVD) in tissues enable subterranean rodents to adapt to hypoxic sealed burrows. However, the expression of VEGF is inhibited by decreases in oxygen content, which is different from what obtains in Sprague Dawley (SD)rats. Thromspondin-1(TSP-1) is the first endogenous angiogenesis inhibitor identified inp53 pathway. It has several domains that bind to different proteins which regulate cell-to-cell interactions, inhibit endothelial cell proliferation and induce endothelial cell apoptosis (anti-angiogenesis). In this study, we analyzed the coding region and the expression pattern of TSP-1 gene in plateau zokor under different oxygen partial pressures using bioinformatics and qRT-PCR, respectively. Our results showed that the base and amino acid homologies between plateau zokor and Northern Israeli blind subterranean mole rat (Nannospalaxgalili) were 95.08 and 97.61%, respectively. There were eight parallel evolution sites with Nannospalaxgalili. Evaluation by ‘Sorting Tolerant From Intolerant' (SIFT) algorithm showed four sites with significant effects on the function of TSP-1. Three-dimensional (3D) structures revealed that Asp185 and Thr270 were located in the NH2 terminal domain, with Glu536 in the Type I repeat domain, and Thr1092 in the COOH terminal domain. Compared to SD rats, the polarities of these four mutation sites changed. The expression levels of TSP-1 in plateau zokor tissues increased significantly from 2 260 m(16.12kPa) to 3 300 m(14.13kPa), but there was no significant difference in TSP-1 expression in SD rats. In conclusion, due to long-term adaption to the hypoxic environment of sealed burrows, plateau zokor upregulates the expression of TSP-1 to effect anti-angiogenesis. Moreover, mutations in gene structure of TSP-1 may play an important role in inhibiting angiogenesis.